Building your dream horse : - Wilhelm, Charles (Howell Book House, 2005)
Charles Wilhelm's Ultimate Foundation Training has transformed thousands of horses into more responsive, mannerly companions. In this book, Wilhelm trains you to use his tried and true principles in training your horse. Go inside the horse's mind to see how he thinks and learns, so you can communicate in a language your horse understands. Discover why and how foundation training works. Wilhelm's uniquely successful methods will help you build a relationship that's more rewarding for both you and your horse--one that lasts a lifetime. Discover why working with your horse should be fun--and why you should stop if it isn't. Learn to identify your horse's emotional level and personality type. Find out the ten secrets your horse wishes he could tell you. Understand why consistency is essential in establishing desired behavior. Communicate with your horse using the right combination of pressure and release, patience, persistence, and conscientious follow-through. Recognize why it's never, ever the horse's fault.